The words of the Belt & Road Initiative: a Chinese discourse for the world? - Costa, C. M. (The Belt and Road Initiative: An Old Archetype of a New Development Model, 2020)
The Belt and Road Initiative is a Chinese international project, whose importance is recognised by the number and variety of academic studies developed in the last three years. Several academic disciplines are exploring the topic, and there is a multiplication of studies in areas like geopolitics, international relations, economics, management and even history. This interest from different scientific fields on the subject proof not only its relevance but also the possibility of facing a global challenge which will reflect international politics as well as domestic politics in diverse countries. The variety of approaches makes it possible to interpret from different angles the same fact. Since 2013, the first time President Xi Jinping announced the continental and maritime initiative which would lead to the B&RI, the interest on the project has been growing. However, most of the studies concentrate on political and economic data, disregarding the effects of discourse in the construction of the B&RI. Even using the instituting moment of the B&RI in 2013, which was an act of international communication, discourse does not receive researchers’ attention. In this chapter, we argue that discourse is one of the B&RI tools for a global narrative. We provide a study based on the international communication theory, supported by a discourse analysis, which enlightens us in better understanding how the B&RI can be adaptive, a project from the present, representing the past and fostering the future.